PENGARUH BRAND AMBASSADOR DAN CITRA MEREK TERHADAP KEPUASAN KONSUMEN YANG DI MEDIASI OLEH MINAT BELI PRODUK AZARINE DIKALANGAN GENERASI Z - Lituhayu, Megan; Winarso, Widi; Hadita (SINERGI : Jurnal Riset Ilmiah, 2025)
This study aims to examine the influence of Brand Ambassador and Brand Image on Consumer Satisfaction mediated by Purchase Intention of Azarine products among Generation Z. The sampling technique used in this study is purposive sampling, based on Hair's formula. Data were collected through the distribution of questionnaires to 115 respondents. The results show that Brand Ambassador and Brand Image have a significant positive influence on Purchase Intention. Purchase Intention is proven to have a significant positive effect on Consumer Satisfaction. In addition, Brand Ambassador has a significant positive effect on Consumer Satisfaction of Azarine products among Generation Z, while the influence of Brand Image on Consumer Satisfaction is positive but not significant.